PENGEMBANGAN MODEL WEBQUEST PADA MATA PELAJARAN IPS DI SEKOLAH MENENGAH KEJURUAN - Wardani Wardani; Raden Gunawan Sudarmanto; Pargito Pargito (Faculty of Teacher Training and Education, University of Lampung, 2014)
The present research was conducted due to the necessity of various learning model that could increase the motivation and achievement of students. This research aimed to create the effective learning model that is able to increase the students’ achievement seen from the attainment of KKM. The research of this learning model consisted of five stages. The result of this present study was in the form of instructional system or learning stages applied in lesson plan and it has been evaluated by materials expert, the specialist of learning model design, and limited test with the following results; (1) the product of webquest model was successfully developed and it was able to be implemented in learning Social Studies toward students on grade X, (2) the use of Webquest model the interest could increase students’ achievement or in other words could able to enhance the amount of students who passed the KKM.Penelitian ini dilatar belakangi masalah rendahnya motivasi belajar dan hasil belajar siswa. Tujuan penelitian ini adalah menghasilkan model pembelajaran efektif yang dapat meningkatkan motivasi belajar dilihat dari hasil belajar siswa. Penelitian pengembangan ini terdiri dari lima tahap. Produk akhir penelitian ini berupa sistem instruksional atau langkah-langkah pembelajaran yang diaplikasikan dalam RPP, dan telah dievaluasi oleh ahli materi, ahli desain model pembelajaran, serta uji terbatas dengan hasil bahwa; (1) produk model Webquest yang berhasil dikembangkan dapat digunakan dalam pembelajaran IPS siswa, dan (2) model Webquest efektif dalam meningkatkan motivasi belajar siswa dilihat dari dapat meningkatkan hasil belajar siswa atau meningkatkan jumlah siswa yang tuntas KKM.Kata kunci : model webquest, pembelajaran ips, pengembangan